Identification of tight junction modulating lipids - Chen-Quay, Shu-Chih; Eiting, Kristine T; Li, Angela W-A; Lamharzi, Najib; Quay, Steven C (Journal of pharmaceutical sciences, 2009)
Tight junctions (TJs) play an important role in regulating paracellular drug transport. The aim of this study was to identify lipids that rapidly and reversibly alter transepithelial electrical resistance (TER) and/or TJ permeability in epithelial tissue. In this study, we developed a screen for identifying lipids that alter TJ properties. Measurement of TER was used to monitor TJ activity on bronchial/tracheal epithelial tissues using a microtiter format. Among seven groups of lipids tested, four classes were identified as TJ modulators (sphingosines, alkylglycosides, oxidized lipids and ether lipids). Individual lipids within these four classes showed up to 95% TER reduction at noncytotoxic concentrations. Alkylglycosides, however, showed high cytotoxicity and low viability at concentrations (0.2-0.4%) reported to enhance transmucosal absorption (Ahsan et al., 2003, Int J Pham 251: 195-203). Several active lipids also showed enhanced permeation of FITC-labeled dextran (m.w. 3000). Immunofluorescence staining of PGPC-treated cells with antibodies against ZO-1, occludin and claudin 4 showed no detectable changes in TJ structural morphology, indicating that a nondestructive, submicroscopic alteration in TJ function may be involved in TER reduction and permeation enhancement. This study demonstrates that three new classes of lipids, excluding alkylglycosides, show potential utility for transmucosal drug delivery.